Artificial Pancreas: the Argentine experience - Colmegna, Patricio Hernán (2019)
The objective of this work is to present a brief review on the international Artificial Pancreas project. In addition, the local project that led to the first Latin American clinical trials with an Artificial Pancreas will be described. These trials were performed in Buenos Aires during 2016 and 2017. The last trial used an algorithm developed in Argentina and defined as the ARG (Automatic Regulation of Glucose). This procedure and its in silico and clinical results will also be presented in this paper.